Dental fear/anxiety and dental behaviour management problems in children and adolescents: a review of prevalence and concomitant psychological factors - GUNILLA KLINGBERG, & ANDERS G. BROBERG (IAPD and Blackwell, 2007)
In 1982, Winer published a review in Child Development, a leading developmental psychology journal, regarding children’s fearful behaviour in dental settings.